SAT0323 Improvement of Digital Ulcerative Disease in Patients with Systemic Sclerosis is Associated with Better Functional Prognosis. (10th June 2014) - Mouthon, L.; Carpentier, P.; Lok, C.; Clerson, P.; Gressin, V.; Hachulla, E.; Bérezné, A.; Diot, E.; Khau Van Kien, A.; Jego, P.; Agard, C.; Modeste Duval, A.-B.; et al.
Abstract : Background: Ischemic digital ulcers (DU) represent a major complication of systemic sclerosis (SSc) leading to hand disability. Objectives: We investigated the impact of controlling the ulcerative disease on hand disability and quality of life in SSc patients following one year of bosentan treatment Methods: ECLIPSE is a 2-year prospective, observational study. Patients with SSc who experienced at least one DU in previous year and received bosentan to prevent occurrence of new DU were included between October 2009 and March 2011.Demographical and clinical data were collected at inclusion and at 1 year, as well as disability scores (Cochin hand function scale (CHFS), health assessment questionnaire disability index (HAQ-DI)), pain score (Visual Analog Scale), and quality of life (SF-36). A controlled ulcerative disease was defined by healing of all DU present at inclusion and the absence of new ulcer between inclusion and one-year follow-up. Data are presented as means ± standard deviations. Results: Follow-up data were available at one year for 120 patients out of the 190 included patients. Patients' characteristics were similar to those of the overall cohort. Mean age at inclusion and at SSc diagnosis were 54±15 and 44±15 years, respectively. SSc was diffuse in 42% of the cases. At inclusion, patients had been receiving bosentan for 15.6±22.1 months. During the one-year follow-up, 46 (38%) patients experienced an episode of new DU and the incidence of the event was 0.6 event/patient-year [95% confidence interval: 0.44-0.81]. Nevertheless, the proportion of patients with at least one DU decreased from 61% to 22% and the number of DU per patient decreased from 1.4±1.8 to 0.6±1.6 (p<0.0001). In parallel disability scores decreased from 29.4±20.1 to 25.0±20.2 (p=0.005) on the CHFS and from 0.96±0.68 to 0.88±0.73 (p=0.04) for the HAQ-DI; the pain score decreased from 4.3±3.1 to 2.9±2.8 (p<0.0001). Improvements in the physical and mental components of the SF-36 were non-significant except for bodily pain (p=0.04) and mental health (p=0.01). Patients with a controlled ulcerative disease (n=58) significantly improved CHFS (p=0.04), HAQ-DI (p=0.04), and physical component of the SF-36 (p=0.05) compared with patients with an uncontrolled disease (n=62). During the one-year follow-up, 21 (17%) patients discontinued bosentan for an adverse event including 5 patients presenting elevated aminotransferases. Conclusions: In patients with SSc receiving bosentan, a controlled ulcerative disease is associated with a significant attenuation of disability. Disclosure of Interest: L. Mouthon Grant/research support: Actelion France, Pfizer, Consultant for: Actelion France, Pfizer, P. Carpentier Consultant for: Actelion France, C. Lok Consultant for: Actelion France, P. Clerson Consultant for: Actelion France, V. Gressin: None declared, E. Hachulla: None declared, A. Bérezné: None declared, E. Diot: None declared, A. Khau Van Kien: None declared, P. Jego: None declared, C. Agard: None declared, A.-B. Modeste Duval: None declared, A. Sparsa: None declared, E. Puzenat: None declared, M.-A. Richard Consultant for: Actelion France DOI: 10.1136/annrheumdis-2014-eular.5478